New distribution records of Anairetes alpinus (Carriker, 1933) (Aves, Tyrannidae), a highly specialized and endangered bird of Polylepis forests in Junín, Peru - Quispe-Melgar, Harold Rusbelth (2018)
The Ash-breasted Tit-tyrant, Anairetes alpinus (Carriker, 1933) (Aves, Tyrannidae), is an endangered and highly specialized bird that inhabits the Polylepis forests (Rosaceae) of Peru and Bolivia. Here, we report 2 new localities in the department of Junín, central Peru, where it was detected in forests dominated by Polylepis canoi, P. rodolfo-vasquezii, and a third undescribed Polylepis species. We conclude that a residential population is the more likely possibility although the possibility of dispersal individuals should also be considered.